Pengembangan Model Pembelajaran Gerak Dasar Nomor Lompat Berbasis Permainan Tradisional di Sekolah Dasar: (Development of Basic Motion Learning Models Based on Traditional Games in Primary Schools) - Shaputra, Roni Zakaria; Flora, Rostika; Sukirno, Sukirno (Jurusan Pendidikan Olah Raga dan Kepelatihan FKIP Universitas Jambi, 2020)
This study aims to develop a basic motion learning model jumping numbers based on traditional games in elementary schools. The method in this study is a method of development with procedures in research, namely: (1) Requirement analysis, (2) Initial model, (3) Validation of the initial model, (4) Description of expert validation data, (5) Revision of the initial model draft, ( 6) Small group outcome data, (7) Revision of the model after the small group trial, (8) Large group outcome data, (9) Model revision after the large group trial. This research was conducted at SDN 02 Sungai Pinang. In this study, the results of questionnaire questionnaire validation obtained from expert validators namely the physical education teacher on the draft product model of jump-based learning numbers on average game 3.8 so that it is included in the valid category. The results of student motivation questionnaire analysis obtained a percentage of 86.4% while the t-test results obtained were 12,387 with ttable = 3.24 then tcount = 12.387> ttable 3.24 as well as the results of the validation of psychomotoric results of students in both 64% categories, and 32% categories very good, obtained tcount of 15.601 with ttable 2.667 which is stated tcount> ttable. So it can be concluded that the new learning model or game-based Jump learning model given to students is valid, practical, and effective to make students motivated to learn jump-based games and actively move in learning and can already be used in the game-based jump learning process in Primary Schools ( SD). Abstrak. Penelitian ini bertujuan untuk mengembangkan model pembelajaran gerak dasar nomor lompat berbasis permainan tradisional di sekolah dasar. Â Metode dalam penelitian ini adalah metode pengembangan dengan prosedur dalam penelitian, yaitu : (1) Analisis kebutuhan, (2) Model awal, (3) Validasi model awal, (4) Deskripsi data validasi ahli, (5) Revisi draft model awal, (6) Data hasil kelompok kecil, (7) Revisi model setelah uji coba kelompok kecil, (8) Data hasil kelompok besar, (9) Revisi model setelah uji coba kelompok besar. Penelitian ini dilakukan di SDN 02 Sungai Pinang. Pada penelitian ini didapatkan hasil validasi angket kuisioner dari validator ahli yaitu guru penjaskes pada draf produk model pembelajaran nomor lompat berbasis permainan rata-rata 3,8 sehingga sudah masuk dalam kategori valid. Hasil analisis kuisioner motivasi siswa didapat persentase sebesar 86,4%sedangkan hasil t-test yang didapat adalah 12.387 dengan ttabel = 3,24 maka thitung = 12.387> ttabel 3,24serta hasil validasi hasil psikomotorik siswa kategori baik 64%, dan 32% kategori sangat baik, didapatkan thitung sebesar 15,601 dengan ttabel 2,667 yang dinyatakan thitung>ttabel. Sehingga disimpulkan bahwa Model pembelajaran baru atau model pembelajaran Lompat berbasis permainan yang diberikan pada siswa valid, praktis, dan efektif untuk membuat siswa termotivasi untuk belajar lompat berbasis permainan serta aktif bergerak dalam pembelajaran dan sudah bisa digunakan dalam proses pembelajaran lompat berbasis permainan di Sekolah Dasar.